2006
DOI: 10.1093/occmed/kql104
|View full text |Cite
|
Sign up to set email alerts
|

University of Toronto case-control study of multiple chemical sensitivity-3: intra-erythrocytic mineral levels

Abstract: IEM measurements do not appear to provide useful diagnostic markers for MCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, no consistent immunodeficiency pattern can be identified among patients with MCS. Specific mineral deficiencies have also not been associated with MCS [3]. Other authors have concluded that all the symptoms in MCS patients stem from specific psychiatric disorders [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, no consistent immunodeficiency pattern can be identified among patients with MCS. Specific mineral deficiencies have also not been associated with MCS [3]. Other authors have concluded that all the symptoms in MCS patients stem from specific psychiatric disorders [4].…”
Section: Introductionmentioning
confidence: 99%